2020
DOI: 10.1016/j.apenergy.2019.114365
|View full text |Cite
|
Sign up to set email alerts
|

The role of electricity in decarbonizing European road transport – Development and assessment of an integrated multi-sectoral model

Abstract: Despite regulation efforts, CO 2 emissions from European road transport have continued to rise. Increased use of electricity offers a promising decarbonization option, both to fuel electric vehicles and run powerto-x systems producing synthetic fuels. To understand the economic implications of increased coupling of the road transport and electricity sectors, an integrated multi-sectoral partial-equilibrium investment and dispatch model is developed for the European electricity and road transport sectors, linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 35 publications
(26 reference statements)
0
39
0
Order By: Relevance
“…Allowing competition for all these options is important to achieve a costeffective green transition. Previous studies do not optimise investments in, for instance, CCS units ( [6], [8], [9], [10], [11]), or transmission expansion [11].…”
Section: Contribution To Literaturementioning
confidence: 98%
See 2 more Smart Citations
“…Allowing competition for all these options is important to achieve a costeffective green transition. Previous studies do not optimise investments in, for instance, CCS units ( [6], [8], [9], [10], [11]), or transmission expansion [11].…”
Section: Contribution To Literaturementioning
confidence: 98%
“…Hedegaard [10] showed that electric cars with grid-to-vechicle and vehicle-to-grid facilitate larger wind power investments. Helgeson [11] illustrated the benefit of coupling and cooptimising the electricity and transport sectors, and Schiebahn [12] investigated the techno-economic feasibility of power-togas in a case study in Germany, concluding that the costs of the related technologies need to decrease to become attractive.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors further pointed out that "it is a deception that European policy classified electric cars as zero emission vehicles." In relation to this last statement, there would be an increase in the production of electrical energy in Europe; according to [26], the "road transport sector [will drive] an additional electricity demand of 1200 TWh in EU in 2050," also ensuring that "the costs of production and replacement (of the fuel by electricity) have been wrongly calculated. "…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another bottom-up approach is agent-based modeling, which is often highly complex and may involve many agent attributes but have been successfully used for evaluating the future market shares of electric vehicles [17]. The sector specific CO 2 reduction targets were evaluated with an integrated multi-sectoral model that combined the European electricity production and road transport [18]. The model enabled estimating the required share of electrified vehicles and increased electric energy demand in the future.…”
Section: Introductionmentioning
confidence: 99%